2017
DOI: 10.1080/14786419.2017.1320795
|View full text |Cite|
|
Sign up to set email alerts
|

Chemical constituents from Gueldenstaedtia verna and their anti-inflammatory activity

Abstract: A new triterpenoid glycoside (1) and 15 known compounds (2-16) were isolated from the whole plants of Gueldenstaedtia verna. The new compound (1) was identified as complogenin 22-O-β-d-glucopyranoside by extensive spectroscopic techniques including 1D (H and C) and 2D NMR experiments (HSQC, HMBC and NOESY), HR-DART-MS and chemical methods. Most of the isolates were evaluated for their inhibitory activities on LPS-induced NO production in RAW 264.7 cells. The inhibitory effects of the active compounds, sulphure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 17 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…Compounds 7 – 20 were identified as 3,4-dihydroxybenzaldehyde ( 7 ), 4-hydroxybenzaldehyde ( 8 ), isovanillin ( 9 ), 3-hydroxy-4-methoxybenzoic acid ( 10 ), 3′,4′-dihydroxyacetophenone ( 11 ), syringic acid ( 12 ), salvianolic acid A ( 13 ), methyl salvionolate A ( 14 ), caffeic acid ( 15 ), 4-hydroxycinnamic acid ( 16 ), isoferulic acid ( 17 ), methyl ( R )-3-(3,4-dihydroxyphenyl)-2-hydroxypropanoate ( 18 ), rosmarinic acid ( 19 ), and methyl rosmarinate ( 20 ), respectively, based on the comparisons of their physical data with reported values.…”
Section: Resultsmentioning
confidence: 99%
“…Compounds 7 – 20 were identified as 3,4-dihydroxybenzaldehyde ( 7 ), 4-hydroxybenzaldehyde ( 8 ), isovanillin ( 9 ), 3-hydroxy-4-methoxybenzoic acid ( 10 ), 3′,4′-dihydroxyacetophenone ( 11 ), syringic acid ( 12 ), salvianolic acid A ( 13 ), methyl salvionolate A ( 14 ), caffeic acid ( 15 ), 4-hydroxycinnamic acid ( 16 ), isoferulic acid ( 17 ), methyl ( R )-3-(3,4-dihydroxyphenyl)-2-hydroxypropanoate ( 18 ), rosmarinic acid ( 19 ), and methyl rosmarinate ( 20 ), respectively, based on the comparisons of their physical data with reported values.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the identification of genistein, the fractionation and HPLC isolation of UCME identified eight compounds, including an isoflavone (lupinalbin A [18]), three phenolic acids ( p -hydroxybenzoic acid [19], salicylic acid [20], and vanillic acid [19]), two fatty acids (monomethyl succinate [21] and 1,10-decanedioic acid [22]), and two steroids (a mixture of β -sitosterol and stigmasterol [23]). Their structures (Figure 5) were identified by comparing their spectroscopic data with data in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has shown that hyperoside exerts an obvious protective effect on liver tissue and that its mechanism is related to its antioxidant activity, by which it promotes the return of NO to normal levels and improves SOD activity [ 51 ]. New research on sulfuretin has shown that this polyphenol can inhibit inflammation [ 52 ]. These four substances are responsible for the protective effects of Shoumei polyphenols against CCl 4 -induced liver injury.…”
Section: Discussionmentioning
confidence: 99%